Lectern with IHS inscription - Ghosh, Ayan (2023)
Lectern (Bible stand) with IHS Monogram of the Holy Name of Jesus. IHS stands for the first three letters of 'Jesus' in the Greek language: Iota (I), Eta (H in capitalized form in Greek), and Sigma (S). In Latin, the inscription came to stand for Jesus, Savior of Humankind, derived from Iesus (Jesus) Hominum (of humankind) Salvator (Savior).